[UIII{N(SiMe2tBu)2}3]: A Structurally Authenticated Trigonal Planar Actinide Complex. Issue 45 (21st September 2014) - Goodwin, Conrad A. P.; Tuna, Floriana; McInnes, Eric J. L.; Liddle, Stephen T.; McMaster, Jonathan; Vitorica‐Yrezabal, Inigo J.; Mills, David P.
Abstract We report the synthesis and characterization of the uranium(III) triamide complex [UIII(N**)3] [1, N**=N(SiMe2tBu)2−]. Surprisingly, complex 1 exhibits a trigonal planar geometry in the solid state, which is unprecedented for three‐coordinate actinide complexes that have exclusively adopted trigonal pyramidal geometries to date. The characterization data for [UIII(N**)3] were compared with the prototypical trigonal pyramidal uranium(III) triamide complex [UIII(N")3] (N"=N(SiMe3)2−), and taken together with theoretical calculations it was concluded that pyramidalization results in net stabilization for [UIII(N")3], but this can be overcome with very sterically demanding ligands, such as N**. The planarity of 1 leads to favorable magnetic dynamics, which may be considered in the future design of UIII single‐molecule magnets.